A time-based process model of international entrepreneurial opportunity evaluation - Chandra, Yanto (Journal of International Business Studies, 2017)
This article investigates two important research gaps in international business (IB): how entrepreneurs evaluate international entrepreneurial opportunities (IEOs) and the role of time in the evaluation process. Drawing on the literature on decision-making models and the philosophical foundation of opportunity, this study employs Gioia’s methodology and content analysis to examine how the founders of 15 early-internationalizing firms evaluated IEOs in the early- and late-stage of internationalization. The findings reveal that the interaction of time and three general rules of IEO evaluation that I coin ‘simple’, ‘revised’, and ‘complex’ influenced the entrepreneurs’ decisions. The findings show that the founders transitioned from simple to revised and to complex rules in the IEO evaluation process and that various contingent factors such as time pressure, resource availability, and type of stakeholders drove these transitions. The three general rules correspond to what I label as ‘opportunity actualization’, ‘revision’, and ‘development maximization’ processes, respectively. I propose a Time-based Process model that reconciles extant internationalization models’ (i.e., Process, Network, Economics, and Entrepreneurship) different explanations regarding why and how firms internationalize.